2011
DOI: 10.1128/aem.02779-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methanogenic Inhibitors on Methane Production and Abundances of Methanogens and Cellulolytic Bacteria in In Vitro Ruminal Cultures

Abstract: The objective of this study was to systematically evaluate and compare the effects of select antimethanogen compounds on methane production, feed digestion and fermentation, and populations of ruminal bacteria and methanogens using in vitro cultures. Seven compounds, including 2-bromoethanesulphonate (BES), propynoic acid (PA), nitroethane (NE), ethyl trans-2-butenoate (ETB), 2-nitroethanol (2NEOH), sodium nitrate (SN), and ethyl-2-butynote (EB), were tested at a final concentration of 12 mM. Ground alfalfa ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
85
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 33 publications
21
85
1
Order By: Relevance
“…From this trial, nitrate-N could be used as an electron acceptor in place of CO 2 . However, Zhou et al (2011) showed that sodium nitrate also significantly decreased methanogen population using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…From this trial, nitrate-N could be used as an electron acceptor in place of CO 2 . However, Zhou et al (2011) showed that sodium nitrate also significantly decreased methanogen population using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…This prompted the hypothesis that headspace gas composition, CO 2 in particular, which is in exchange with H 2 CO 3 /HCO 3 − in the medium, depending on concentration, acid-base balance and gas pressure, may affect fermentation characteristics and gas production in ruminal in vitro cultures. A range of initial headspace composition of in vitro cultures has been reported, including 100% CO 2 (Anderson et al, 2003;Weimer et al, 2005), 100% N 2 (Hoover et al, 1976) and a mixture of gases typical of an anaerobic chamber (85% N 2 , 10% H 2 , and 5% CO 2 ; Zhou et al, 2011;Patra et al, 2012). Patra and Yu (2013) investigated the effects of three different headspace gases (N 2 + CO 2 + H 2 in the ratio of 90:5:5, 100% CO 2 , and 100% N 2 ) and the interaction with type of substrate (alfalfa hay or alfalfa hay and concentrate) and media bicarbonate concentration on gas and CH 4 production.…”
Section: Headspace Gas Compositionmentioning
confidence: 99%
“…However, monensin is relatively nonspecific and impairs beneficial processes, like acetic acid formation by acetogenic bacteria (7,8). Other antimethanogenesis compounds that have been developed include 2,4-bis (trichloromethyl)benzo [1,3] dioxins (9), an inhibitor of methanopterin biosynthesis (10), and nitrogen oxides (nitrate, nitrite, NO, and N 2 O) (11)(12)(13)(14). Whereas the former two compounds have complex structures, the third is simple.…”
Section: Pope Francis (2)mentioning
confidence: 99%